Ant diversity (Hymenoptera: Formicidae) and predation by ants on the different stages of the sugarcane borer life cycle Diatraea saccharalis (Lepidoptera: Crambidae) - De Oliveira, Roseli de Fátima; De Almeida, Luiz Carlos; De Souza, Débora Rodrigues; Munhae, Catarina Bortoli [UNESP]; Bueno, Odair Correa [UNESP]; Morini, Maria Santina de Castro (Biology Centre, AS CR, 2012)
The sugarcane borer Diatraea saccharalis is an important pest of sugarcane and ants are one of its main predators. The practice of burning sugarcane straw in situ after harvest has been gradually replaced in Brazil by other practices. However, it is unknown whether ants can control the abundance of this borer in the presence of straw. In this study, we assessed the diversity and species composition of ants attacking different stages of the pest's life cycle. Specifically, we asked whether the species richness and abundance of ants varies during the course of day and a year. We established one-hectare plots at random locations in a sugarcane plantation. Once a month, we collected 20 samples of each stage of the D. saccharalis life cycle and randomly distributed these samples as bait on plants spaced 20 m apart within a plot. Ants were collected daily in the morning and afternoon over a period of 12 months. We identified several aspects of ant feeding behaviour that may affect their biological control of the borer: (1) the greatest number of ants were collected from baits consisting of the immature stages of the sugarcane borer, (2) ants were most active in the morning and (3) their activity varied from month to month. Solenopsis saevissima and morphotypes of Crematogaster sp.7 and Pheidole sp.35 are potentially important predators of borers in sugarcane crops in which the straw is not burnt.
Keywords: Biological control; Diatraea saccharalis; Formicidae; Hymenoptera; Mechanical cultivation